Field-Osgood family papers - Field, Susan K. Osgood; Osgood, Maria Bowne Franklin; Osgood, Samuel, 1748-1813.
Correspondence, speeches and writings, household financial accounts, legal papers, genealogical material, printed matter, photographs, lithographs, and engravings chiefly dating from 1780 to 1930. Includes personal financial papers of Samuel and Maria Bowne Franklin Osgood; correspondence (1814-1821) of Susan K. Osgood Field with her sisters living near Troy, N.Y., and Andover, Mass., and with a cousin in Charleston, S.C., reflecting everyday life of young women in the nineteenth century; sermons of David Osgood (1747-1822), brother of Samuel Osgood; manumission papers from New York State and a letter of Maria Bowne Franklin Osgood concerning her obligations to Chloe Field, an African American woman; letter (1846) from poet Robert Browning to Hickson Woolman Field; and papers (1917-1919) of William B. Osgood Field relating to World War I aerial photography, the U.S. Army Signal Corps, and the Military Intelligence Division, U.S. War Dept.; and papers of the related Bradhurst family.
Library of Congress Prints and Photographs Division.
Family members include Samuel Osgood (1748-1813), member of the Continental Congress and U.S. Board of Treasury, first U.S. postmaster general, and New York State legislator; his wife, Maria Bowne Franklin Osgood; their daughter, Susan K. Osgood Field; and their descendants.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Browning, Robert, -- 1812-1889 -- Correspondence; Field, Chloe; Field, Hickson W. -- 1823- -- Correspondence; Field, William B. Osgood; Osgood, David, -- 1747-1822.; Bradhurst family; Field family; Osgood family; United States. -- Army. -- Signal Corps; United States. -- Board of Treasury; United States. -- Continental Congress; United States. -- War Department. -- Military Intelligence Division; Sermons, American -- 18th century; Slaves -- Emancipation -- New York (State); World War, 1914-1918.; World War, 1914-1918 -- Photography; Young women -- United States -- 19th century; Andover (Mass.) -- Social life and customs; Charleston (S.C,) -- Social life and customs; New York (State) -- Politics and government -- 1775-1865.; Troy (N.Y.) -- Social life and customs; United States. -- Postmaster General